Tree Diversity in Nepal: An updated list - Pandey, Tirtha Raj (Journal of Plant Resources, 2024)
Trees are one of the dominant life forms in plant world. They have important ecological and commercial roles in society. Nepal is also rich in terms of tree species diversity; however, a comprehensive country-wide inventory is still in need. This paper aims to document the occurrence of native and naturalized tree species of the country with updated information on their identification and nomenclatural issues. Extensive database searches including the ‘Global Tree Search’ and consultation of many publications has revealed the occurrence of 700 taxa of trees belonging to 90 families, 300 genera and 688 species in Nepal. During the study, 8 species of trees are found as endemic to Nepal, while 8 other tree species are naturalized in the country. Knowing the diversity and distribution of tree species will help in the formulation of their conservation strategy and estimation of their ecological value.